PREVALENCE OF REFRACTIVE ERRORS IN MADRASSA STUDENTS OF HARIPUR DISTRICT - Atta, Zoia; Arif, Abdus Salam; Ahmed, Iftikhar; Farooq, Umer (Journal of Ayub Medical College Abbottabad, 2015)
Background: Visual impairment due to refractive errors is one of the most common problems among school-age children and is the second leading cause of treatable blindness. The Right to Sight, a global initiative launched by a coalition of non-government organizations and the World Health Organization (WHO), aims to eliminate avoidable visual impairment and blindness at a global level. In order to achieve this goal it is important to know the prevalence of different refractive errors in a community. Children and teenagers are the most susceptible groups to be affected by refractive errors. So, this population needs to be screened for different types of refractive errors. The study was done with the objective to find the frequency of different types of refractive errors in students of madrassas between the ages of 5-20 years in Haripur. Methods: This cross sectional study was done with 300 students between ages of 5-20 years in Madrassas of Haripur. The students were screened for refractive errors and the types of the errors were noted. After screening for refractive errors-the glasses were prescribed to the students. Results: Myopia being 52.6% was the most frequent refractive error in students, followed by hyperopia 28.4% and astigmatism 19%. Conclusion: This study showed that myopia is an important problem in madrassa population. Females and males are almost equally affected. Spectacle correction of refractive errors is the cheapest and easy solution of this problem.